Amplitude of low-frequency fluctuations in classical trigeminal neuralgia patients with purely paroxysmal and concomitant continuous pain - Zhao, He; Xie, Shenghui; Ma, Xueying; Bai, Xue; Song, Yuanjun; Wu, Qiong; Gao, Yang (Frontiers in Pain Research, 2025)
BackgroundPurely paroxysmal neuralgia (PP-CTN) and concomitant continuous pain (CCP-CTN) are different subtypes of classical trigeminal neuralgia (CTN). Our aim was to explore the common and unique spontaneous brain activity abnormalities between subtypes.MethodsA total of 101 PP-CTN patients, 52 CCP-CTN patients, and 122 age- and sex-matched healthy controls (HCs) were included. All the subjects underwent resting-state functional magnetic resonance imaging, and changes in spontaneous brain activity were observed via whole-brain static amplitude of low-frequency fluctuation (sALFF) and dynamic amplitude of low-frequency fluctuation (dALFF).ResultsCompared with HCs, PP-CTN patients presented significantly lower sALFF values in the left calcarine fissure and surrounding cortex (CAL), left putamen, and left Rolandic operculum (ROL). Compared with HCs, CCP-CTN patients presented significantly increased sALFF values in the left superior frontal gyrus (SFG), right medial superior frontal gyrus (MSFG), left putamen, right insula, and brainstem. Compared with the PP-CTN group, the CCP-CTN group presented significantly greater sALFF values in the left CAL, left SFG, right MSFG, left putamen, right insula, left ROL and brainstem. The results of the dALFF analysis revealed that, compared with HCs, PP-CTN patients presented increased dALFF values in the anterior cingulate gyrus (ACG) and decreased dALFF values in the right cuneus. Compared with HCs, CCP-CTN patients presented increased dALFF values in the ACG, right insula, and brainstem and decreased dALFF values in the right cuneus. Compared with the PP-CTN group, the CCP-CTN group presented increased dALFF values in the right insula and brainstem.ConclusionsOur findings reveal different neural mechanisms between PP-CTN and CCP-CTN patients, providing important neuroimaging evidence to better understand the pathophysiology of different subtypes of CTN.